In vitro cytotoxicity assay of Fucoidan extracted from Turbinaria conoides against cancer cell lines MCF7, A549, and normal cell line L929 - Revathi Chitra Santhanam; Syed Ali Mohammed Yacoob; Anuradha Venkatraman (Universidade de São Paulo, 2022)
Abstract The main aim of the study is to quantify the cytotoxic property of the Fucoidan extracted from the Turbinaria conoides using the MTT assay with the standard fucose. Fucoidan was extracted using the soaked water method and it was determined using the HPLC procedure the obtained Test sample Fucoidan extracted from the Turbinaria conoides and standard fucose was subjected to the cytotoxicity assay against the MCF7 Human breast cancer cell line, A549 lung cancer cell line, and L929 normal mouse fibroblast cell line. From the results it was found that the Test sample showed good IC50 value for MCF7 cell line then A549 with an increasing concentration 24 hours incubation at 37°C The IC50 for MCF7 was 115.21 µg/ml and A549 396.46µg/ml and the Fucoidan extract was checked for its cytotoxicity against the normal mouse fibroblast cell line L929, Fucoidan was found non-lethal to the L929 mouse fibroblast normal cell line. Standard fucose also gave a significant result towards MCF7 and against the L929. This indicates that the Fucoidan extracted from Tubinaria conoides shows better anticancer potential in it. Hence its application can be further extended in the pharmacological fields.